Stroke Prevention in Atrial Fibrillation and Valvular Heart Disease - Ahmad, Saad (Open Cardiovasc Med J, 2016)
There is a clinically staggering burden of disease stemming from cerebrovascular events, of which a majority are ischemic in nature and many are precipitated by atrial fibrillation (AF). AF can occur in isolation or in association with myocardial or structural heart disease. In the latter case, and when considering health at an international level, congenital and acquired valve-related diseases are frequent contributors to the current pandemic of AF and its clinical impact. Guidelines crafted by the American Heart Association, American College of Cardiology, European Society of Cardiology and Heart Rhythm Society underscore the use of vitamin K antagonists (VKAs) among patients with valvular heart disease, particularly in the presence of concomitant AF, to reduce the risk of ischemic stroke of cardioembolic origin; however, the non-VKAs, also referred to as direct, target-specific or new oral anticoagulants (NOACs), have not been actively studied in this particular population. In fact, each of the new agents is approved in patients with AF not caused by a valve problem. The aim of our review is to carefully examine the available evidence from pivotal phase 3 clinical trials of NOACs and determine how they might perform in patients with AF and concomitant valvular heart disease.